2017
DOI: 10.1136/bmjstel-2017-000225
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cognitive load and emotional states during multidisciplinary critical care simulation sessions

Abstract: BackgroundThe simulation in critical care setting involves a heterogeneous group of participants with varied background and experience. Measuring the impacts of simulation on emotional state and cognitive load in this setting is not often performed. The feasibility of such measurement in the critical care setting needs further exploration.MethodsMedical and nursing staff with varying levels of experience from a tertiary intensive care unit participated in a standardised clinical simulation scenario. The emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
44
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 31 publications
2
44
0
9
Order By: Relevance
“…Regarding the test–retest reliability, the extraneous CL was the least stable factor among the three identified factors in the Chinese version MDT‐CL. The possible reason might include the following: (a) there are only three items included in the extraneous CL and Leppink et al (Leppink et al, ) indicated that the stability of a scale or subscale can be affected when there are only few items within a scale or subscale and (b) extraneous CL may vary when the participant's emotions (Pawar et al, ) or the physical environment (Aldekhyl, Cavalcanti, & Naismith, ) is subject to change. Future studies are needed to conduct equivalence reliability for testing the stability of the extraneous CL (Park et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the test–retest reliability, the extraneous CL was the least stable factor among the three identified factors in the Chinese version MDT‐CL. The possible reason might include the following: (a) there are only three items included in the extraneous CL and Leppink et al (Leppink et al, ) indicated that the stability of a scale or subscale can be affected when there are only few items within a scale or subscale and (b) extraneous CL may vary when the participant's emotions (Pawar et al, ) or the physical environment (Aldekhyl, Cavalcanti, & Naismith, ) is subject to change. Future studies are needed to conduct equivalence reliability for testing the stability of the extraneous CL (Park et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the correlation between extraneous CL and germane CL (r = 0.003) in our study is different than the original study (r = −0.19). If a nursing care activity is presented to a nurse in a simple or familiar way, and there is a lower extraneous CL, it seems that the nurse may devote more cog- (Pawar et al, 2018) or the physical environment (Aldekhyl, Cavalcanti, & Naismith, 2018) is subject to change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of test–retest reliability, ‘patient‐focused emotional suppression’ was the least stable of the three factors in the C‐ELS for nurses. This may be due to changes in participants' emotions (Pawar, Jacques, Deshpande, Pusapati, & Meguerdichian, 2018) and external environment (Aldekhyl, Cavalcanti, & Naismith, 2018). Therefore, for stability testing, equivalent reliability testing is also required in further research.…”
Section: Discussionmentioning
confidence: 99%
“…3 During the stress of a delivery room resuscitation, noise, time pressure, and the use of unfamiliar medications increase the risk of dosing errors. 4,5 Epinephrine is used infrequently during neonatal resuscitation. Timely administration of the correct dose may be lifesaving.…”
mentioning
confidence: 99%